Implementation of the Ecosystem Services Approach in German Biosphere Reserves - Plieninger, Tobias; Woltering, Manuel; Job, Hubert (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
To safeguard ecosystem services has been defined as a central goal for large protected areas in several international agreements. This study investigates the importance of the ecosystem services approach for biosphere reserves in Germany. The ecosystem services approach can be useful in various fields for large protected areas, e. g. as approach in communication, fundraising, monitoring, planning and management. The analysis of the evaluation reports of the currently 15 UNESCO biosphere reserves in Germany shows a high variation in the degree of implementing the ecosystem services approach. The biosphere reserves at the North Sea coast are leading, possibly as they are subject to the trilateral agreement on the Wadden Sea, as the evaluation reports are fairly new, and they have better equipped management, being biosphere reserves and national parks at the same time. Important barriers of the implementation of the ecosystem services approach may arise from limited resources and from the administrative allocation of reserve management to environmental ministries, which is in conflict with the cross-sectoral character of the ecosystem services approach.